The birth of a nation [videorecording (DVD)] - Parker, Nate, 1979-; Parker, Nate, 1979-; Hammer, Armie, 1986-; Miller, Penelope Ann (20th Century Fox Home Entertainment, 2016)
Nat Turner is a literate American slave and preacher. His financially strained owner accepts an offer to use Nat's preaching to subdue unruly slaves. But as Nat witnesses countless atrocities, he orchestrates an uprising in the hopes of leading his people to freedom.